Tingkat Kerentanan Fisik Bencana Kebakaran Permukiman Di Kelurahan Bidara Cina Kecamatan Jatinegara Kota Administrasi Jakarta Timur - Riska Annisa Azzahra; Asma Irma Setianingsih; Muzani Jalaluddin (Pendidikan Geografi Universitas Muhammadiyah Prof. Dr. Hamka, 2026)
This study focuses on analyzing and mapping physical fire vulnerability in densely populated areas to reduce risk exposures caused by close-knit building patterns and the lack of portable fire extinguishers. The study employed a descriptive quantitative (scoring) method utilizing eight parameters: building density, building material, building age, availability of Light Fire Extinguishers (APAR), absolute distance to the fire station, road conditions, road width, and response time. Data were collected through documentation, questionnaires, and secondary data. The analytical techniques used include scoring, class classification, Normalized Difference Built-Up Index (NDBI), overlay, buffer distance analysis, and descriptive analysis. The sample involved 64 Neighborhood Units (RTs) across 6 Community Units (RWs): 12 RTs in RW 03, 15 RTs in RW 06, 4 RTs in RW 013, 9 RTs in RW 014, 10 RTs in RW 015, and 14 RTs in RW 016. The research findings indicate that the physical vulnerability level to settlement fire disasters across the 64 RTs in 6 RWs is distributed into low vulnerability (RW 03, RW 013, RW 016) at 50% and medium vulnerability (RW 06, RW 014, RW 015) at 50%. The physical vulnerability area of each RW is: RW 03 (4.51 ha), RW 06 (6.17 ha), RW 013 (0.85 ha), RW 014 (2.15 ha), RW 015 (2.79 ha), and RW 016 (2.67 ha). The study area is dominated by dense settlements. All sampled buildings are permanent structures with an age of more than 20 years. There are 18 APAR units available across categories of 'sufficiently complete' and 'incomplete'. Furthermore, the location is close to the fire station (< 2.5 km); road widths vary between > 6 m and < 4 m; road conditions consist of asphalt and concrete; and the fire department's response time from Jatinegara Sub-district, Bukit Duri Urban Village, and Rawajati Urban Village is < 15 minutes, which is considered successful.